2015
DOI: 10.3233/rnn-150501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implantable peroneal nerve stimulation on gait quality, energy expenditure, participation and user satisfaction in patients with post-stroke drop foot using an ankle-foot orthosis

Abstract: Implantable FES improved the use of residual ankle plantarflexion motion, ankle power of the paretic leg and step length symmetry compared to using an AFO, however, not resulting in decreased energy expenditure or improved participation. User satisfaction was highest with FES, but this was not related to the observed gait improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Previous studies showed the clinical effectiveness of an implanted FES to improve patients' gait (Burridge et al, 2007(Burridge et al, , 2008Chantraine et al, 2016;Ernst et al, 2013;Hausmann et al, 2015;Klaus Daniel Martin et al, 2015;Schiemanck et al, 2015), but no studies have so far assessed its effect on brain plasticity. Only one animal study explored the changes occurring in the brain (as measured by Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed the clinical effectiveness of an implanted FES to improve patients' gait (Burridge et al, 2007(Burridge et al, , 2008Chantraine et al, 2016;Ernst et al, 2013;Hausmann et al, 2015;Klaus Daniel Martin et al, 2015;Schiemanck et al, 2015), but no studies have so far assessed its effect on brain plasticity. Only one animal study explored the changes occurring in the brain (as measured by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the electrical stimulation is delivered in between the ipsilateral foot lift and strike (i.e., the entire swing phase). This technique has been shown to improve patients' gait (Burridge et al, 2007;Chantraine, Schreiber, Kolanowski, & Moissenet, n.d.;K Daniel Martin, Polanski, Schackert, & Sobottka, 2015;Klaus Daniel Martin et al, 2015) in terms of walking speed as well as ankle kinematic pattern, and is well-tolerated in patients with stroke (Schiemanck et al, 2015) and multiple sclerosis (Hausmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some systemic reviews of AFO have reported that gait training with AFO can improve walking ability and balance in people with stroke 1 , 15 ) . However, few studies have focused on the correlation between AFO and motor performance changes of the lower limb in post-stroke patients 16 , 17 , 18 ) . Changes seen in this study were more marked in the lower-limb motor performance, with a substantial clinically meaningful change in fast walking speed (0.13 m/s) being achieved by all participants who completed the study protocol.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Some studies of implanted peroneal FES systems have shown indications of an improved gait pattern and gait symmetry as well. [35][36][37] Calf muscle weakness Unfortunately, there is currently no treatment option that effectively compensates for calf muscle weakness. There are some indications that it is possible to improve the propulsion symmetry between the legs in patients with stroke through targeted training, either by increasing gait speed with or without FES 38,39 or by walking on a treadmill with body weight support.…”
Section: Pes Equino(varus)mentioning
confidence: 99%